Synthesis, crystal structure, and stability of n-lupinylphthalimide conformers - Turdybekov, K.M.; Nurkenov, O.A.; Nurmaganbetov, Zh.S.; Satpaeva, Zh.B.; Turdybekov, D.M.; Makhmutova, A.S.; Fazylov, S.D. (Journal of Structural Chemistry, 2020)
As a result of studying the interaction of chlorolupinine with potassium phthalimide, the optimal synthesis conditions for N-lupinylphthalimide by the Gabriel method are identified. The crystal structure of N-lupinylphthalimide is determined for the first time by single crystal XRD. The energy characteristics are calculated using the quantum chemical method. It is found that the conformer with the chair conformation of the cycles with the axial orientation of the phthalimide substituent is more stable than that with the equatorial orientation.
Keywords: single crystal XRD; quantum chemical calculations; conformational analysis; N-lupinylphthalimide; lupinine derivatives